Impact of mixing state on aerosol optical properties during severe wildfires over the Euro-Mediterranean region - Majdi, Marwa; Kim, Youngseob; Turquety, Solene; Sartelet, Karine (Atmospheric environment (1994), 2020)
The impact of mixing state of particles from biomass burning on aerosol optical properties (aerosol optical depth (AOD) and single-scattering albedo (SSA)) is studied over the Euro- Mediterranean region during the severe fire event in the Balkans between 20 and 31 July 2007, also characterized by high dust concentrations. When the mixing state is resolved in chemistry-transport models, chemical compounds are grouped for computational reasons, and internal mixing is assumed within each group. Up to six groups are defined here (dust, black carbon, two inorganic groups and two organic groups). The influence of different grouping assumptions is studied here and compared to the influence of the distribution of black carbon (BC) in particles (“pure homogeneous” representation and “core-shell” one), and the influence of modeling the water absorbed by both inorganic and organic compounds. The comparisons of simulated AODs to observations from the surface network AERONET show that AOD is slightly underestimated when aerosol compounds are assumed to be externally mixed and slightly overestimated when they are assumed to be internally mixed. The mixing state of dust with other compounds, as well as the distribution of BC in particles, strongly influence the optical properties. The impact of the mixing state on AOD is higher than the impact of the distribution of BC in particles, reaching 8–12% on average over the fire regions and 16% in the fire plume. Analysis related to the impact of particle mixing state and BC distribution on SSA shows results similar to AOD. The impact of the mixing state on SSA can reach −8.5% over the fire regions and it is higher than the impact of the BC representation, which is lower than 2%. At the location of fires, water absorbed by inorganics and organics is shown to influence the AOD by about 2%, which is in the lower range of the influence of water on AOD over the region (between 0 and 40%). This low influence of water on AOD during fire is due to assumptions made in the modelling, where most of secondary organic aerosols formed during fires are assumed to be hydrophobic. •Water absorbed by inorganics and organics enhances optical properties.•Mixing-state representation matters more than black-carbon distribution in particles.•The mixing state of dust needs to be considered separately from other compounds.